Synthesis and biological evaluation of new tri-heterocyclic derivatives as anti-colorectal cancer agents - Benjamin Victoir; Océane Pertegaz; Elfi Ducrocq; Marion Polomski; Maxime Guéguinou; William Raoul; Cécile Croix; Gildas Prié (Results in Chemistry)
Colorectal cancer is a major health problem, with a poor prognosis if not detected at early stage. It is the third most common cancer worldwide and the second most deadly. Thus, discovering new treatments became an absolute priority for many research laboratories to improve the prognosis. The involvement of STAT3/5 in the development of colorectal cancer is well established and has led to the development of new inhibitors of these proteins. This work was guided by the previous identification of a potent STAT5 inhibitor in the fight against myeloid leukemias. Pharmacomodulations were strategically performed, and the in vitro activities of all tri-heterocyclic derivatives were assessed on HT29 and Lovo colorectal cancer cell lines, as well as on the non-tumoral NCM356 colonic epithelial cell line derived from normal mucosa. Compared with 5-fluorouracil classically used in the treatment strategy for colorectal cancer patients, some of our compounds showed better activity on cancer cells. In particular, compound 1b blocked the growth of colorectal cancer cells at sub-micromolar concentrations, thus represents a promising lead compound in the fight against colorectal cancer.